Effect of Supplementation With Selenium-Yeast on Muscle Antioxidant Activity, Meat Quality, Fatty Acids and Amino Acids in Goats - Tian, Xing-Zhou; Li, Jia-Xuan; Luo, Qing-Yuan; Wang, Xu; Xiao, Mei-Mei; Zhou, Di; Lu, Qi; Chen, Xiang (Frontiers in Veterinary Science, 2022)
The objective of this study was to observe the effects of selenium-yeast (SY) on growth performance, muscle antioxidant activity, meat quality, fatty acid and amino acid profiles in growing goats. A total of 18 Qianbei-pockmarked goats were assigned to 3 groups (6 duplicates per group) by body weight (25.75 ± 1.75 kg; mean ± standard deviation) according to a completely randomized design: 1) basal diet (CON); 2) CON with 2.4 g/d SY (LS); and 3) CON with 4.8 g/d SY (HS). The results indicated that goats receiving SY did not show any differences (P > 0.05) in terms of dry matter intake, growth performance, or muscle chemical composition. The HS group showed a significant increase (P < 0.05) in the dressing percentage, eye muscle area and meat color, as well as muscle total antioxidant capacity, glutathione peroxidase and 2,2-diphenyl-1-picrylhydrazyl scavenging activity levels, whereas it showed a significant drop (P < 0.05) in shear force and muscle malondialdehyde levels relative to the control. Feeding 4.8 g/d SY led to a significant (P < 0.05) decrease in the levels of C8:0, C14:0, C15:0, C16:0, C17:0, C18:0, C20:0 and total saturated fatty acids, whereas it led to a significant (P < 0.05) increase in C15:1 in comparison with that of the control group. Compared with the control group, the treatment groups had higher (P < 0.05) levels of C18:1n9, C22:4, and monounsaturated fatty acids. In addition, the HS group had significantly higher (P < 0.05) muscle serine, valine, isoleucine, leucine, ornithine hydrochloride, methionine, and tyrosine levels than the control group. Collectively, Se supplementation in the diet did not affect growth performance, whereas it could improve meat quality, muscle antioxidant activity, fatty acid and amino acid profiles in Qianbei-pockmarked goats. This showed that the optimal accession SY level was 4.8 g/d under the experimental conditions of this study.